Impact of a contrast media volume control device on acute kidney injury rate in patients with acute coronary syndrome. Issue 1 (18th July 2020) - Briguori, Carlo; Golino, Marco; Porchetta, Nicola; Scarpelli, Mario; De Micco, Francesca; Rubino, Carmine; Focaccio, Amelia; Signoriello, Giuseppe
Abstract: BACKGROUND: The DyeVert™ system (Osprey Medical Inc., Minnesota, MN) may reduce contrast media (CM) volume during coronary procedures while maintaining fluoroscopic image quality. Here, we assessed whether the use of the DyeVert system reduces acute kidney injury (AKI) rate in patients with acute coronary syndrome (ACS) undergoing invasive coronary procedures. METHODS: ACS patients scheduled for coronary procedure from January 2017 to December 2019 were included. Two groups were identified: (a) Control group ( n  = 339), including patients in which a conventional manual injection syringe was used; and (b) DyeVert group ( n  = 112), in which CM injection was handled by the DyeVert™ system. A propensity score matching was performed to reduce the effect of treatment selection bias and potential confounders. In all cases, a low‐osmolar, nonionic CM was administered. The primary objective was the rate of AKI, defined as a serum creatinine increase ≥0.3 mg/dl within 72 hr after CM exposure. RESULTS: CM volume was higher in the Control group than in the DyeVert group (130 [120–188] ml vs. 99 [69–136] ml; p  <.001). In the DyeVert group the mean percent CM volume saved was 38 ± 13%. AKI occurred in 7/90 patients (8%) in the DyeVert group and in 17/90 (19%) patients in the Control group (odds ratio = 0.37; 95% confidence interval 0.14–0.95; p  =.047). CONCLUSIONS: This preliminary result suggests that CM volume reduction obtained by the DyeVert™ system is an effective strategy to prevent AKI in ACS patients undergoing invasive procedure.